PENGARUH STRUKTUR MODAL, LIKUIDITAS, AKTIVITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN: STUDI EMPIRIS PADA SEKTOR INDUSTRI MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Aini Diana Qisthy Hartono; Slamet Mudjijah (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study aimed to analyze the influence of capital structure, liquidity, activity, and dividend policy affect firm value in the food and baverage manufacturing sub-sector listed on the Indonesia Stock Exchange during 2022-2024. The research uses secondary data drawn from financial reports. From a population of 99 listed companies for the 2022-2024 period, purposive sampling yielded 19 companies as the study sample. A quantive approach was applied, using multiple linear regression for analysis. Data processing and analysis were conducted with Microsoft Excel 2022 and IBM SPSS version 27. The findings indicate the capital structure has a positive and statistically significant effect on firm value. While liquidity, activity, and dividend policy show no significant effect.